Slow mapping in color word acquisition across languages: evidence from Japanese children - Yang, Jiale; Dobkins, Karen; Wagner, Katie; Sakuta, Yuiko; Kanazawa, So; Yamaguchi, Masami K. (Frontiers in Developmental Psychology, 2025)
It is well-known that children have a delay between their first production of color words and acquisition of adult-like understanding. A previous study showed that this delay could be attributed to a process of gradually converging on language-specific color word boundaries. In this study, we tested this account in a second language, Japanese. We presented 12 color samples to children and then conducted production and comprehension tasks to check whether children have adult-like understanding of color words. Our results were consistent with previous findings showing that children before acquiring adult-like understanding tend to use color words systematically as overextensions of adult meanings. These results indicate that the delay between production and adult-like understanding of color words reflects a gradual process of learning language-specific color boundaries, potentially shared across languages.